INFLUENCE OF PRODUCT QUALITY, PRICE, PROMOTION AND BRAND IMAGE TO PURCHASING DECISIONS AND THEIR IMPACT ON CUSTOMER SATISFACTION THERE ARE DRINKS IN TEH PUCUK HARUM - Bangkit Hutomo Putra; Muchsin Saggaf Shihab (Jurnal Scientia, 2023)
Study This done For prove Influence Quality Product, Price, promotion, And Image Brand To Decision Purchase And Impact To Satisfaction Customer On drink In Packaging Tea Shoots Harum, with a sample of 60 people, the sampling technique uses the method random sampling . Data Which used is data primary in form questionnaire. Hypothesis study This is influence significant from Quality Product, Price, promotion, And Image Brand To Decision Purchase And Impact To Satisfaction Customer On drink In Packaging Tea Shoots Fragrant. Collection data use questionnaire with scale Likert And analyzed with method PLS (Partial Least Square). Results study This show that (1) Quality product influential significant to decision customer And satisfaction consumer (2) Price No influential significant to customer decisions and consumer satisfaction (3) Promotion influential significant to decision customer but promotion No influential significant to satisfaction consumer (4) Image brand No significant effect on customer decisions and consumer satisfaction (5) Decision purchase No impact to satisfaction customer.